KAJIAN KAPAL BERBENDERA INDONESIA YANG MELAKUKAN PENANGKAPAN IKAN TANPA SURAT IZIN PENANGKAPAN IKAN ANDON DITINJAU DARI UNDANG-UNDANG PERIKANAN: STUDY OF INDONESIAN FLAG VESSELS CARRYING OUT FISHING WITHOUT ANDON FISHING PERMITS REVIEWED FROM THE FISHERIES LAW - Romariotua; Sri Untari Indah Artati (Faculty of Law, Universitas Trisakti, 2024)
Andon Fishing Permit is a written permit that must be owned by every fishing vessel to catch fish outside its administrative domicile area, but there are still parties who catch fish outside their domicile without an Andon SIPI as in Decision Number 23/Pid.Sus-PRK/2021/PN Lbj. The problem is 1) How are fishing business activities carried out by Indonesian-flagged vessels without an Andon Fishing Permit in Decision Number 23/Pid.Sus-PRK/2021/PN Lbj. reviewed from the Fisheries Law? 2) Is the Decision of the Labuan Bajo District Court Number 23/Pid.Sus-PRK/2021/PN Lbj. in accordance with the Fisheries Law? This normative legal research. The research shows that fishing outside the administrative domicile without an Andon Fishing Permit (SIPI) is prohibited under Law Number 45 of 2009 in conjunction with Ministerial Regulation KP Number 25 of 2020. Decision Number 23/Pid.Sus-PRK/2021/PN Lbj. aligns with Article 27 paragraph 1 of the Fisheries Law 2009. The conclusion is that fishing without a permit violates the Fisheries Law, and the court's decision complies with the legal provisions.